APPLICATION OF INTEGRATED COOPERATIVE MODELS READING AND COMPOTION (CIRC) ON STUDENT LEARNING OUTCOMES - Juli Maini Sitepu; Dian Septi Arum Sari; Melyani Sari Sitepu (Proceeding International Seminar of Islamic Studies, 2021)
This research is motivated by the application of a learning model that is less attractive to social studies subjects in class III SDN Kalongan 02, causing students to be bored with social studies so that learning outcomes are not optimal.The research method used is a quasi-experimental research.The study population was all third grade students at SDN Kalongan 02 East Ungaran Semarang Regency.The sample was selected bycluster samplingwith a sample size of 62 students (31 students in the Experiment class and 31 students in the Control class). The results showed that there was a difference in lerning outcomes in social studies between using the Cooperative Integrated Reading and Composition (CIRC) model in the Experiment class getting the highest score of 95, while the conventional learning model in the Control.Class getting the highest score of 57.5.Learning outcomes in a class using theCooperative Integrated Reading and Composition(CIRC)modelincreased compared to the control class with a difference of 37.5.Keywords: Integrated Reading Model, Compotion Model (CIRS), Learning Outcomes